PENERAPAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA KELAS VI DI SDN 16 SUNGAI PINYUH - Hayati, Nur; Setyowati, Dessy; Farisi, Salman Al (Universitas Tanjungpura, 2025)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) activities within the context of the independent curriculum, as well as to explore how these activities can enhance students' competencies and character. The method used is qualitative descriptive research, with data collection through interviews and observations. The focus of this research includes the implementation of holistic, contextual, student-centered, and exploratory principles (P5).In the implementation of the Pancasila Student Profile Strengthening Project (P5), students are invited to participate in various activities relevant to the theme